Development of an PBL-Based Augmented Reality Media for Enhanced Social and Natural Science Learning Outcomes in Elementary School Students - Maharani, Dinda Syavira; Fathurrahman, Moh. (FKIP Universitas Lampung, 2025)
Development of an PBL-Based Augmented Reality Media for Enhanced Sosial and Natural Science Learning Outcomes in Elementary School Students. Objectives : This research aims to develop ARIFAL media, which is packaged in the form of Augmented Reality and interactive PowerPoint Presentation based on Problem-Based Learning to improve the learning outcomes of social science students in grade IV. The media is designed to make learning more interactive, engaging, and effective in enhancing students' conceptual understanding. Method : The study uses Research and Development (R&D) with the Borg and Gall model, involving 5 students in a small-scale trial and 20 students in a large-scale trial at SD Negeri 2 Tubanan. Data collection was conducted through tests and non-tests, including observations, questionnaires, interviews, and documentation. The effectiveness of the media was evaluated through expert validation and improved student learning outcomes. Finding : The results of specialist validation show that this media is highly feasible for use, with material validity of 88% and media validity of 96%. The trial implementation demonstrated a significant increase in students' learning outcomes, with an average pretest score of 46.40 increasing to 85.40 in the posttest, and an N-Gain of 0.74 (high category). Furthermore, teachers and students gave very positive responses, indicating that the media is both useful and engaging.Conclusion: It can be concluded that ARIFAL media, which integrates Augmented Reality and interactive PPT based on Problem-Based Learning, effectively improving social science learning outcomes. This media can be applied in elementary school education to increase student engagement and understanding. Keywords: augmented reality interactive PPT, science and technology learning outcomes, problem-based learning model.